Microtus pennsylvanicus - James H. Honacki; Kenneth E. Kinman; James W. Koeppl (Alien Press, Inc. & The Association of Systematics Collections, 1982)
Microtus pennsylvanicus (Ord, 1815). In Guthrie, A new geogr., hist., comml., grammar. Philadelphia, 2nd Amer, ed., 2:292. REVIEWED BY: R. E. Barry, Jr. (REB); J. Ramirez-Pulido (JRP). TYPE LOCALITY: U.S.A., Pennsylvania, "meadows below Philadelphia." DISTRIBUTION: North America from Newfoundland to W. Alaska, north into tundra zone, south to Georgia, N. Great Plains, S. Rocky Mtns. (U.S.A.), isolated population in N. Chihuahua (Mexico). COMMENT: Subgenus Microtus; see Anderson, 1960. Includes chihuahuensis; see Bradley and Cockrum, 1968, Am. Mus. Novit., 2325:3-7. Klimkiewicz, 1970, Mammalia, 34:640-665, suggested that pennsylvanicus is conspecific with agrestis. This species requires review over its entire range and comparison with related Old and New World species (SRL). Closely related insular forms, such as breweri, provectus (here included in pennsylvanicus), nesophilus and others may best be considered subspecies; see Chamberlain, 1954, J. Mammal., 35: 587, Fivush et al., 1975, J. Mammal., 56:272, and Wheeler, 1956, Evolution, 10: 176- 186. Hall, 1981, considered breweri and nesophilus distinct species and provectus a subspecies of pennsylvanicus, whereas Anderson, 1959:496, afforded all full specific status, without elaborating; see comments under breweri and nesophilus. Reviewed by Reich, 1981, Mamm. Species, 159:1-8. See Anderson and Hubbard, 1971, Am. Mus. Novit., 2460:1-8, for discussion of distribution. ISIS NUMBER: 5301410008080035001. Published as part of James H. Honacki, Kenneth E. Kinman & James W. Koeppl, 1982, Order Rodentia (Part 4), pp. 477-504 in Mammal Species of the World (1 st Edition), Lawrence, Kansas, USA :Alien Press, Inc. & The Association of Systematics Collections on page 496, DOI: 10.5281/zenodo.7353034